Application of natural compounds in the treatment and prevention of prediabetes - Chen, Jie; Jin, Li; Chen, Mengyao; Xu, Kai; Huang, Qi; He, Beihui (Frontiers in Nutrition, 2023)
Prediabetes is an intermediate stage in the development of type 2 diabetes mellitus characterized by impaired fasting glucose and/or impaired glucose tolerance. Prediabetes generally has no obvious clinical symptoms, and most patients are found in health examinations or due to other diseases. Reactive hypoglycemia may indicate the possibility of early diabetes. Without effective preventive measures, prediabetes can progress to diabetes leading to serious public health problems. Therefore, early diagnosis and intervention are important. Many animal experiments and clinical trials have proven that natural compounds substantially improve glucose metabolism disorder. The active ingredients are mainly alkaloids, polysaccharides, saponins, terpenoids, flavonoids and polyphenols. Their mechanism of action mainly involves improved insulin sensitivity and insulin resistance, inhibited activity of alpha-glucosidase, antioxidant activity, anti-inflammatory, regulation of gut microbiota and activating of peroxisome proliferator-activated receptor-γ. This paper reviews the mechanisms of action of natural compounds on prediabetes and the status of related research.